An Integrated Global‐To‐Regional Scale Workflow for Simulating Climate Change Impacts on Marine Ecosystems - Kelly Ortega‐Cisneros; Denisse Fierros‐Arcos; Max Lindmark; Camilla Novaglio; Phoebe Woodworth‐Jefcoats; Tyler D. Eddy; Marta Coll; Elizabeth Fulton; Ricardo Oliveros‐Ramos; Jonathan Reum; Yunne‐Jai Shin; Cathy Bulman; et al. (Earth's Future)
Abstract As the urgency to evaluate the impacts of climate change on marine ecosystems increases, there is a need to develop robust projections and improve the uptake of ecosystem model outputs in policy and planning. Standardizing input and output data is a crucial step in evaluating and communicating results, but can be challenging when using models with diverse structures, assumptions, and outputs that address region‐specific issues. We developed an implementation framework and workflow to standardize the climate and fishing forcings used by regional models contributing to the Fisheries and Marine Ecosystem Model Intercomparison Project (FishMIP) and to facilitate comparative analyses across models and a wide range of regions, in line with the FishMIP 3a protocol. We applied our workflow to three case study areas‐models: the Baltic Sea Mizer, Hawai'i‐based Longline fisheries therMizer, and the southern Benguela ecosystem Atlantis marine ecosystem models. We then selected the most challenging steps of the workflow and illustrated their implementation in different model types and regions. Our workflow is adaptable across a wide range of regional models, from non‐spatially explicit to spatially explicit and fully‐depth resolved models and models that include one or several fishing fleets. This workflow will facilitate the development of regional marine ecosystem model ensembles and enhance future research on marine ecosystem model development and applications, model evaluation and benchmarking, and global‐to‐regional model comparisons.